VESSEL DENSITY OF SUPERFICIAL, INTERMEDIATE, AND DEEP CAPILLARY PLEXUSES USING OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY - Lavia, Carlo; Bonnin, Sophie; Maule, Milena; Erginay, Ali; Tadayoni, Ramin; Gaudric, Alain (Retina (Philadelphia, Pa.), 2019)
To provide values of retinal vessel density (VD) in the three retinal capillary plexuses, foveal avascular zone (FAZ) area, and retinal layer thickness in a cohort of healthy subjects. The optical coherence tomography angiography maps of 148 eyes of 84 healthy subjects, aged 22 to 76 years, were analyzed for measuring VD of the retinal capillary plexuses, using the Optovue device comprising a projection artifact removal algorithm. Foveal avascular zone metrics were measured, and the relationship between optical coherence tomography angiography findings and age, sex, and image quality was studied. The deep capillary plexus showed the lowest VD (31.6% ± 4.4%) in all macular areas and age groups compared with the superficial vascular plexus (47.8% ± 2.8%) and intermediate capillary plexus (45.4% ± 4.2%). The mean VD decreased by 0.06%, 0.06%, and 0.08% per year, respectively, in the superficial vascular plexus, intermediate capillary plexus, and deep capillary plexus. Mean FAZ area, FAZ acircularity index, and capillary density in a 300-µm area around the FAZ were 0.25 ± 0.1 mm, 1.1 ± 0.05, and 50.8 ± 3.4%, respectively. The yearly increase in FAZ area was 0.003 mm (P < 0.001). The deep capillary plexus, a single monoplanar capillary plexus located in the outer plexiform layer, has the lowest VD, a significant finding that might be used to evaluate retinal vascular diseases. Vascular density decreased with age in the three capillary plexuses.